2008
DOI: 10.1158/1535-7163.mct-08-0124
|View full text |Cite
|
Sign up to set email alerts
|

Thymoquinone inhibits tumor angiogenesis and tumor growth through suppressing AKT and extracellular signal-regulated kinase signaling pathways

Abstract: Thymoquinone, a component derived from the medial plant Nigella sativa, has been used for medical purposes for more than 2,000 years. Recent studies reported that thymoquinone exhibited inhibitory effects on cell proliferation of many cancer cell lines and hormone-refractory prostate cancer by suppressing androgen receptor and E2F-1. Whether thymoquinone inhibits tumor angiogenesis, the critical step of tumor growth and metastasis, is still unknown. In this study, we found that thymoquinone effectively inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
210
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 309 publications
(223 citation statements)
references
References 29 publications
12
210
1
Order By: Relevance
“…It is reported that in prostate cancer PC3 cells, thymoquinone may suppress tumor angiogenesis and growth by downregulating AKT and extracellular signal-regulated kinase (ERK) signaling (17). Additionally, thymoquinone notably suppressed DNA synthesis and proliferation in prostate cancer LNCaP, C4-2B, DU145 and PC3 cell lines via inactivation of the androgen receptor (AR) and E2F1, a regulator of cell viability (18).…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that in prostate cancer PC3 cells, thymoquinone may suppress tumor angiogenesis and growth by downregulating AKT and extracellular signal-regulated kinase (ERK) signaling (17). Additionally, thymoquinone notably suppressed DNA synthesis and proliferation in prostate cancer LNCaP, C4-2B, DU145 and PC3 cell lines via inactivation of the androgen receptor (AR) and E2F1, a regulator of cell viability (18).…”
Section: Discussionmentioning
confidence: 99%
“…cancer diseases, including cervical cancer (Effenberger et al, 2010), blood cancer (El-Mahdy et al, 2005), hepatic cancer (Thabrew et al, 2005), colon cancer (Salim and Fukushima, 2003), pancreatic cancer (Chehl et al, 2009), skin cancer (Salomi et al, 1991), fibrosarcoma (Awad, 2005), renal cancer (Khan and Sultana, 2005), prostate cancer (Yi et al, 2008), and breast cancers (Farah and Begum, 2003;Ahmad et al, 2012). Pharmacologically important components of N sativa extracts have also been studied against lung cancer as an anticancer agent.…”
Section: Introductionmentioning
confidence: 99%
“…30 Similarly, Thymoquinone, a phytochemical compound found in the plant Nigella sativa, inhibits tumor angiogenesis and tumor growth by suppressing extracellular signal-regulated kinase signaling pathways. 31 Until now, although antiangiogenic molecules dominantly target endothelial cells and exhibit effective control of tumor angiogenesis, the finding of a natural product-derived single compound to control the tumor mass via the marked delay of tumor angiogenesis, particularly through the modulation of stem/progenitor cells bioactivities, are largely unknown.…”
Section: Resultsmentioning
confidence: 99%